Exhaustion of vascular access in a hemodialysis patient with end stage renal disease: A case report - Pham, Hien Van; Tram, Toan Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Introduction: Vascular access is a vulnerable aspect of hemodialysis in patients with end-stage renal disease. In such cases, arteriovenous fistulas are preferred, instead of catheters. Moreover, failure of the current arteriovenous access and catheter dependence often lead to morbidity and mortality. Case report: A 76-year-old female patient presented with reduced vascular access secondary to progressive central venous stenosis. Consequently, an alternative access was created via the popliteal vein. This vein has been used in cases of patients undergoing emergency hemodialysis who did not have vascular access via other conventional routes. Conclusion: Unusual vascular access for emergency hemodialysis is necessary when other routine veins cannot be accessed. The use of arteriovenous fistulas instead of catheterization should be encouraged during the initial hemodialysis stage